Optimizing stocking density for enhanced growth and survival of a cyprinid fish (G. theunensis) fry in cage cultivation environment - Duangjai, Ekachai; Punroob, Jittra; Punroob, Natthawoot (Creative Science, 2025)
The impact of stocking densities on the growth and survival of a cyprinid fish (G. theunensis) fry was thoroughly investigated in a comprehensive study aimed at identifying optimal aquaculture conditions. This research utilized a Complete Randomized Design (CRD) with three replicates for each of four different stocking densities: 50 100 150 and 200 fry m-³ over a three-month period from October to December 2024. Fish were fed a commercial fish feed containing 28% protein twice daily. The study found no significant differences (P>0.05) in the survival rates across the different densities with rates ranging from 73.83% to 82.67%. However, the lowest density (50 fry m-³) resulted in a significantly higher final length of 5.93 cm, compared to 5.40 cm, 5.19 cm, and 5.03 cm for the 100, 150, and 200 fry m-³ densities, respectively. Similarly, fish at the 50 fry m-³ density achieved a significantly higher final weight of 4.88 g, compared to 4.08 g, 3.92 g, and 3.90 g for the higher densities. The daily gain was highest at the lowest density, measuring 0.05 g fish-1 day-1, versus slightly lower gains at higher densities. Specific growth rate: The rate at 50 fry m-³ was 157.95% fish-1 day-1, substantially higher than those observed at higher densities. Weight Gain: Demonstrated a similar pattern, with the 50 fry m-³ density achieving a 612.77% gain, significantly outperforming the other densities. Feed Conversion Ratio: The FCR was most efficient at the lowest density (2.34) worsening progressively at higher densities. GRAPHICAL ABSTRACT HIGHLIGHTS The lowest stocking density (50 fry/m³) resulted in the best growth performance, with the highest final length (5.93 cm), weight (4.88 g), and daily weight gain. Survival rates showed no significant differences across densities, ranging from 73.83% to 82.67%. The feed conversion ratio (FCR) was most efficient at the lowest density (2.34) and worsened as stocking density increased.